Designing the smart organization how breakthrough corporate learning initiatives drive strategic change and innovation - Deiser, Roland (Jossey-Bass, 2009)
"Increased competition in the international marketplace and the volatile and ever-changing economic landscape have put the spotlight on corporate learning as a business function that can help determine and sustain long-term business success." "Written by Roland Deiser - an internationally acclaimed expert on building strategic capabilities into large-scale systems - Designing the Smart Organization outlines an innovative paradigm of corporate learning that can help any organization achieve remarkable results. In this groundbreaking book, Deiser abandons the traditional thinking about corporate learning and redefines it as the core engine for building sustainable "strategic competence" into the DNA of a firm. Thus corporate learning becomes an indispensable enabler of continuous strategic innovation and change." "Designing the Smart Organization provides a framework for a more comprehensive and strategic perspective of the corporate learning agenda that puts special emphasis on integrating learning interventions with the strategic process of the firm. To demonstrate how this process drives the boundaries of the practice way beyond the established notion of simple training and management education, the book is filled with case studies from leading companies and organizations including ABB, EADS, Siemens, Novartis, BASF, PricewaterhouseCoopers, and the U.S. Army. These studies reveal how leading large-scale and cutting-edge global corporations are using the power of dynamic corporate learning approaches to drive innovation, enhance cultural values, master post-merger integration, transform business models, build technological expertise, foster strategic change processes, and ultimately increase bottom-line results." "For any company that wants to compete in the twenty-first century, Designing the Smart Organization offers inspiring perspectives for integrating corporate learning as a core business practice that will create sustainable strategic and organizational capabilities."--BOOK JACKET